Performance, energy balance, and emission characteristi-cs of a spark ignition engine fueled with gasoline and LPG - Marthen Paloboran; Thesya Atarezcha Pangruruk; Ismail Rahim; Juhamri Juhamri; Auliya Rahmatul Ummah; Erlyne Nadhilah Widyaningrum (Politeknik Negeri Lhokseumawe, 2026)
Efforts to reduce greenhouse gas emissions continue to encourage the transition from liquid fossil fuels to gaseous fuels, as gaseous fuels are expected to provide cleaner combustion and lower hydrocarbon emissions. This study aimed to evaluate the performance of a spark ignition engine with a carburetor fuel system operated using gasoline and Liquefied Petroleum Gas (LPG), and to analyze its energy balance based on the First Law of Thermodynamics. The energy balance consisted of input energy from air and fuel, useful output energy, and energy losses during combustion. The engine was operated at speeds ranging from 2000 to 5000 rpm. Fuel consumption was measured after the engine consumed 50 mL of gasoline and 50 g of LPG. The results showed that emissions of HC, CO, and CO2 from LPG were lower than those from gasoline. The useful energy produced by LPG combustion was lower than that of gasoline; however, LPG showed higher thermal efficiency due to lower Specific Fuel Consumption (SFC) and reduced energy losses. The conversion from gasoline to LPG in a carburetor system reduced emissions by approximately 7–73%, whereas the average reduction in an electronic fuel injection system was reported at 11–15%.